Magnetic properties and crystal structure of Ga2−xFexO3. Issue 3 (25th May 2018) - Yan, Hui; Huang, Yuanqi; Cui, Wei; Zhi, Yusong; Guo, Daoyou; Wu, Zhenping; Chen, Zhengwei; Tang, Weihua
Abstract : Ga2− x Fe x O3 (GFO) bulks with x from 0.7 to 1.3 have been fabricated using the classic solid-state route. The structural, optical, and magnetic properties have been investigated systematically. X-ray diffraction spectra and FULLPROF profile fitting indicate that GFO bulks belong to the orthorhombic structure with the space group Pc 21 n . Phase separation appears at the Fe content of x = 1.3. The optical bandgap decreases almost linearly with the increase of iron content, which means that the bandgap of GFO bulks can be controlled by adjusting the Fe content in the samples. The magnetic property measurements suggest that GFO is ferromagnetic, and the magnetic properties are enhanced compared with other reported works, exhibiting the application in ferromagnetic semiconductors devices.